Bełkot techniczny jako przejaw polszczyzny konsumpcyjnej - Jachimowska, Katarzyna (Acta Universitatis Lodziensis. Folia Linguistica, 2015)
The article draws the attention to, described by Kazimierz Ożóg, symptom of consumptive Polish language like technical gibberish. Its characteristics comprise amongst other: using a list of technical parameters of a device, which does not warrant a disclosure of product benefits and its functionalities; accumulation of foreign names supplemented with numbers, letter symbols and acronyms; unusual semantic cohesion of words used for the purpose of exaggeration; technical foreign terminology. Analysed in the article informational-persuasive language acts directed at modern technology products, are symptoms of currently popular consumerism, which leads to a creation of promotional and marketing technical gibberish.